(untitled) - Scazzero, Peter; (1956-...) (U.S.A, 2015)
In The Emotionally Healthy Leader, bestselling author Peter Scazzero equips leaders to answer God's call to develop a deep, inner life with Christ, examining its profound implications for planning, decision making, building teams, creating healthy culture, and carrying out our mission in the world. There is an immense difference between a Christian and a secular leader. Secular leaders learn best practices and strategies from the most successful global leaders and then do their best to implement them. They are secular in that they manage to lead without God. While we can, and should, learn from best secular leadership practices, Christian leadership is different. Christian leaders lead from an interior life with Jesus Christ. Our lives are defined by Jesus who calls us to follow Him and do His will. We lead from a position of dependence and communion with Him. Moreover, our vision is more than earthly measures of success. Christian leaders lead people to Jesus so that their lives might be powerfully transformed by Him. Yet we cannot give what we do not possess. We must be increasingly transformed first. The first half of The Emotionally Healthy Leader looks at four foundational areas often overlooked in developing leaders: facing our shadow, leading out of our marriage or singleness, slowing down for loving union with Jesus, and practicing Sabbath delight. Who we are, our `being`, is primary, impacting all our exterior activity. Scazzero then examines the intersection of our inner lives with the practical, everyday `doing` of leadership - planning and decision-making, culture and team buildings, community and dual relationships, and endings and new beginnings. Forged out of hard lessons learned in 26 years of leading a large, growing, complex, missional, multiracial church in New York City, The Emotionally Healthy Leader offers a unique integration of how who we are profound impacts what we do as leaders. It looks at how all our decisions and activities each day flow out of our inner walk with Christ. The Emotionally Healthy Leader goes beyond a quick fix or a new technique to core, beneath-the-surface issues of uniquely Christian leadership. This book is more than a book you will read
Keywords: Christian Leadership